(untitled) (Tempo e Argumento, 2009)
The immigration experiences, as a part of the identities process, usual in the diasporic dynamics, take with them the construction of new relationships between the “I” and the “others”. In fact, the forms of self-representation and of experiencing the space-time went through a strong transformation, creating hybridized individuals. This typical process of the immigration phenomenon, that produces the contact and comparison with the new alterities, enrich and intensify a dynamic of recreation of the realms of memory that make sense in the new reality. The main objective of this paper is to identify and to narrate some mnemonic places that have been built in the last ten years of the South American immigration in Italy, considering the life story of Brazilian and Argentinean women. We can observe that some spaces – physical places or individual/collective experiences – occupied a special dimension in the immigration narratives, becoming part of a mnemonic liturgy of a diasporic life